META-ANALYSIS OF THE INFLUENCE OF ICT BASED PHYSICS LEARNING MEDIA ON THE LEARNING OUTCOMES OF SENIOR HIGH SCHOOL STUDENTS - Nadilla Rahmi Fitri; Renol Afrizon; Hidayati -; Hufri - (PILLAR OF PHYSICS EDUCATION, 2022)
In the 21st century, information and communication technology has developed rapidly. Changes in the learning system to be student-centered. One of the principles of the 2013 curriculum is that students learn from various learning sources. Learning resources can be in the form of print media or electronic media. When studying, teachers rarely connect physics with everyday life, whereas nowadays, the wording many learning media that can explain physics in everyday life. Research on physics learning media has done a lot. This study has a purpose, namely to see the impact of ICT-based physics learning media on senior high school student learning outcomes. The research method is meta-analysis. Articles published in 2011-2021. The article consisted of 17 national articles and three international articles that met the predetermined criteria to be processed to calculate the effect size. Effect size is calculated based on five categories, namely grade level, ICT-based learning media, learning materials, online/offline ICT-based media, and student learning outcomes. The research results obtained (1) ICT-based learning media gave the highest effect in class XI, namely 1,87. (2) ICT-based learning media gives the highest effect on Adobe Flash media, which is 3,30. (3) the learning material gives the highest effect on the rigid body equilibrium material, which is 5,50. (4) online/offline ICT-based media have the highest effect on offline media, namely 1,41. (5) learning outcomes have the highest effect on the knowledge aspect, namely 1,28. Therefore, ICT-based physics learning media has a good effect on student learning outcomes.